2016
DOI: 10.4102/koedoe.v58i1.1357
|View full text |Cite
|
Sign up to set email alerts
|

Viewshed and sense of place as conservation features: A case study and research agenda for South Africa's national parks

Abstract: Sense of place (SoP) refers to the meanings and values that people attach to places. The concept can be used to frame how people engage or form a connection with the natural environment. At a sensory level, SoP is influenced by people’s visual experiences, which in turn can be linked to the concept of viewsheds. Viewsheds can be transformed, either abruptly (e.g. by infrastructure development such as wind turbines) or more gradually (e.g. by non-native trees invading a landscape). In this study, we focus on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
(66 reference statements)
1
16
0
1
Order By: Relevance
“…In accordance, we found that areas with open vegetation (generally attractive to people as they allow views in the distance 31 ), had higher use of social media, and received more likes, across different protected areas in sub-Saharan Africa. Viewsheds are key aspects of the visual landscape affecting visitor’s experiences 32 and part of the sense of place sought by tourists in protected areas 33 . In addition, while in other regions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, we found that areas with open vegetation (generally attractive to people as they allow views in the distance 31 ), had higher use of social media, and received more likes, across different protected areas in sub-Saharan Africa. Viewsheds are key aspects of the visual landscape affecting visitor’s experiences 32 and part of the sense of place sought by tourists in protected areas 33 . In addition, while in other regions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the parks are located in different biomes offering a variety of landscape experiences and aesthetic cultural services. While Kruger NP is located in the Savanna and Thickets biomes, Addo Elephant NP is located in the Fynbos, Forest, Nama-Karoo and the Indian Ocean Coastal Belt biomes (Mucina & Rutherford, 2006 (Barendse et al, 2016;Hausmann, Slotow, Fraser, & Di Minin, 2017). They are both located in the Fynbos biome (Mucina & Rutherford, 2006) and access to the parks is open as they are mostly unfenced.…”
Section: Study Areasmentioning
confidence: 99%
“…From the above discussion, it is clear that place attachment is made up of different dimensions, and that individuals differ in terms of their levels of attachment to a specific place. The same seems to be true in the context of South African National Parks, and Barendse et al (2016) raised specific questions that still remain unanswered in terms of place attachment (sense of place) experiences in South African National Parks, for example, how place attachment experiences vary across groups of visitors. For this reason, we hypothesise that:…”
Section: How Attachment Levels Differ Based On Demographicsmentioning
confidence: 96%
“…According to Halpenny (2010), the value and meaning of place are given by individuals and society, and presented in groups, cultures and individuals. Researchers are increasingly acknowledging the value of the less quantifiable and less tangible advantages that individuals get from nature and places such as protected areas (Barendse et al 2016), for example the recreational, spiritual, experiential and educational exchanges with nature that add to the well-being of a human (Millennium Ecosystem Assessment 2005). More importantly, the extent to which one appreciates such benefits is often dependent on one's ability to engage with or form an association with the natural environment (Hinds & Sparks 2008).…”
Section: Place Sense Of Place and Place Attachmentmentioning
confidence: 99%